Polarização dos macrófagos e sua associação com fatores prognósticos em casos de neoplasias colorretais, considerando a presença e ausência de mutações nas metaloproteinases - Brambilla, Eduardo (My University, 2024)
Background: Macrophages are a component present at the tumoral microenvironment. Given their plasticity, macrophages can either be seen as a neoplastic cell controlling factor or a tumor progression stimulating factor. Furthermore, macrophage polarization may hold prognostic value and manipulation of this condition could potentially be explored to control colorectal neoplasms. Objectives: Therefore, this work aimed to evaluate the M1 and M2 macrophage infiltration rates in colorectal neoplasia cases with presence and absence of metalloproteinase mutation, as well as investigate prognostic factors associated with the disease. Methods: In order to determine macrophage quantity and polarization, two sets of patients diagnosed with colorectal neoplasia were studied: (i) 33 patients with metalloproteinase mutation; and (ii) 33 patients without metalloproteinase mutation. Additionally, prognostic and survival factors associated with colorectal cancer were analyzed. Results: In terms of metalloproteinase mutation, 33 patients (54,1%) did not exhibit mutations, whereas 28 patients (45,9%) showed the referred mutation. When samples were grouped by tumoral stage, 10 were from patients in stage I (16,9%), 19 from stage II (34,2%), 25 from stage III (42,4%) and five from stage IV (8,5%). A total of 12 patient deaths (19,7%) were recorded during this study, seven of which were from the control group (21,2%) and five from the group with mutation (17,9%). The markers CD163 and CD206, indicative for M2 polarized macrophages, resulted in an average of 23 and 17, with a standard deviation of 21 and 17, respectively. On the other hand, the iNOS marker for M1 polarized macrophages returned a mean of five macrophages per site with a standard deviation of 11. Conclusion: The macrophage density observed through these markers did not demonstrate significant statistical differences between groupings with the variables employed in this study, including metalloproteinase mutation, age, gender, tumor region, tumor staging, TILS, tumor recurrence and clinical outcome. In the studied sample, no association was found between macrophage polarization and colorectal cancer prognostic variables, as well as survival. As for metalloproteinase mutation, a better survival rate was obtained for patients with the mutation. [resumo fornecido pelo autor]
Introdução: O macrófago é um componente presente no microambiente tumoral. Devido a sua plasticidade, o mesmo pode se apresentar como um fator de controle das células neoplásicas, bem como um fator de estímulo à progressão tumoral. Além disso, a polarização do macrófago pode ser um fator prognóstico e sua manipulação poderia ser usada para o controle das neoplasias colorretais. Objetivos: Avaliar as taxas de infiltração por macrofagos M1 e M2 em neoplasias colorretais com presença e ausência de mutação para metaloproteinases, além de investigar os fatores prognósticos associados a essa doença. Métodos: Para avaliar a quantidade e polarização dos macrófagos, foram incorporados dois conjuntos de pacientes diagnosticados com neoplasia colorretal: (i) 33 pacientes com mutação na metaloproteinase; e (ii) 33 pacientes sem mutação na metaloproteinase. Além disso, foram analisados os fatores prognósticos e de sobrevida associados ao câncer colorretal. Resultados: Em relação a presença de mutação das metaloproteinases, 33 pacientes (54,1%) não exibiram mutações, enquanto 28 pacientes (45,9%) apresentaram a referida mutação. O estadiamento para agrupamento das amostras, 10 eram provenientes de pacientes em estádio I (16,9%), 19 eram estádio II (34,2%), 25 eram do estádio III (42,4%) e cinco do estádio IV (8,5%). Ocorreram 12 óbitos (19,7%) durante o estudo, sete (21,2%) do grupo controle e cinco do grupo com mutação (17,9%). Os marcadores CD163 e CD206, indicativos para macrófagos polarizados M2, apresentaram médias de 23 e 17, com desvio padrão de 21 e 17, respectivamente. Já o marcador iNOS para macrófagos polarizados M1 apresentou média de cinco macrófagos por campo com desvio padrão de 11. Conclusão: A densidade de macrófagos obtida pelos marcadores não demostrou diferença estatística significativa entre os agrupamentos com as variáveis estudadas de mutação para metaloproteinases, idade, sexo, localização do tumor, estadiamento, TILS, recidiva e desfecho clínico. Na amostra estudada não encontrou-se relação entre a presença de macrófagos polarizados e as variáveis prognósticas do câncer colorretal assim como na sobrevida. Em relação a mutação das metaloproteinases a mesma mostrou uma melhor sobrevida nos pacientes mutados. [resumo fornecido pelo autor]
Keywords: Neoplasias colorretais; Macrófagos associados a tumor; Adenocarcinoma; Colorectal neoplasms; Tumor-associated macrophages; Adenocarcinoma